Effect of Sedation Strategy on the Hospital Length of Stay and ICU Length of Stay after On-Pump Cardiac Surgeries - Yelyzaveta E. Plechysta; Serghii O. Dubrov (Ukrainian Journal of Cardiovascular Surgery, 2023)
Over the past decades, many approaches have been changed in intensive care and in anesthesiology. Most of these changes were included in the guidelines now well known as fast-track protocols (protocols for enhanced recovery after surgery). Cardiac anesthesiology was not an exception. Preoperative, intraoperative and postoperative management of the patient are the main components of these protocols, which are aimed at reducing the length of stay (LOS) of patients in the hospital and intensive care units (ICU).The aim. To detect the relationship between the sedation strategy and the duration of the hospital LOS and the ICU LOS.Materials and methods. This was a randomized, controlled, parallel study. We analyzed 194 patients over 18 years of age who underwent cardiac surgical treatment using artificial blood circulation. Statistical data processing was carried out on the basis of GraphPad Prism 9.0 software.Results. According to our research, the average hospital LOS was 7.779 ± 2.844 days in the propofol group (n = 95), 7.188 ± 1.601 days in the dexmedetomidine group (n = 16). In the group where patients were sedated with a combination of drugs (n = 83), the average length of hospitalization was 5.904 ± 1.535 days. The average ICU LOS was 2.463 ± 1.090 days in the propofol group and 2.375 ± 1.360 days in the dexmedetomidine group. In the group where patients were sedated with a combination of drugs (n = 83), the average ICU LOS was 2.361 ± 0.8776 days. The hospital LOS of patients who were sedated with a combination of drugs was lower (p < 0.0001). When comparing the ICU LOS, no difference was found in all three sedation groups (p = 0.3903).According to the analysis conducted in the propofol group, the ICU LOS was shorter in patients who did not receive vasoactive therapy (p = 0.0299). In the dexmedetomidine sedation group, no difference was found between the ICU LOS in patients with or without vasoactive support (p = 0.5289). In the group of patients who underwent sedation with a combination of drugs, the ICU LOS was shorter in the group of patients who underwent correction with vasoactive drugs (p < 0.0001).Conclusion. Sedation with a drug combination (dexmedetomidine and propofol) may reduce hospital LOS (p < 0.0001). There was no influence of any sedation strategy on the ICU LOS (p = 0.3903). Early initiation of vasoactive support with sedative drug combination (dexmedetomidine and propofol) shortens the ICU LOS (p < 0.0001).